MAHOT SEBAGAI PEMANDU WISATA PADA PUSAT LATIHAN GAJAH DI MINAS SIAK RIAU - Khoiron, Ahmad; Rifiyan, Andi M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The research purposed to get know how mahot role as a tour guide on elephant conservation center in minas siak riau be serving tourist or visitor ones visiting every day.This research used qualitative descriptive method to analyze the problems. The sample in this research are 12 samples by using purposive sampling and accidental sampling. And then the technique to collected data in this research are using observation, interview, and documentation.Based on the research, mahot role as a tour guide already happened in three stages, they are knowledge , skills, and attitude in guiding and service tourist, each has applied however still need clarify the status of elephant conservation center became a tourist destination nature based so mahot gets licence a tuor guide.Key words : Role Mahot, Tour Guide, Elephant Conservation Center Minas